Policy Workshop Mali - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Pictures from workshops in Mali discussing the current status of climate change policies in agriculture in Ghana, Mali, Kenya and Ethiopia. The workshops were organized by the CGIAR Climate Program (CCAFS) in collaboration with with the Council for Scientific and Industrial Research (CSIR) in Ghana, the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) in Mali, the Tegemeo Institute in Kenya and the Climate Change Forum in Ethiopia. The Workshop is being carried out in relations to CCAFS Research Theme 3: Pro-Poor Climate Change Mitigation.